RF Power Amplifiers for Wireless Communications. - Cripps, Steve C. (Artech House, 2006)
Reviewing the previous edition, IEEE Microwave Magazine boasted, ''anyone designing power amplifiers will find this book thought provoking and useful.'' Professionals in the field agreed as the book went on to be one of our top-selling RF design titles. This extensively revised edition of RF Power Amplifiers for Wireless Communications offers practitioners a comprehensive, practical, and up-to-date understanding of how to tackle a PA (power amplifier) design with confidence and quickly determine the cause of malfunctioning hardware. Among the numerous updates, the Second Edition includes five.